Management and organization theory : a Jossey-Bass reader - Miles, Jeffrey A. (San Francisco, CA : Jossey-Bass, 2012)
Management and Organization Theory offers a summary and analysis of the 40 most popular, researched, and applied management and organization theories. This important resource includes key instruments used to measure variables in each theory and examines pertinent questions about the theory: strengths and weaknesses, practical applications, and the seminal articles published on each theory.
1. Absorptive Capacity Theory -- 2. Actor-Network Theory -- 3. Agency Theory -- 4. Agenda Setting Theory -- 5. Attachment Theory -- 6. Attribution Theory -- 7. Balance Theory -- 8. Control Theory -- 9. Diffusion of Innovations Theory -- 10. Dynamic Capabilities Theory -- 11. Efficient Market Theory -- 12. Ethical Theory -- 13. Field Theory; 14: Game Theory -- 15. Goal Setting Theory -- 16. Image Theory -- 17. Institutional Theory -- 18. Knowledge-Based Theory -- 19. Media Richness Theory -- 20. Mental Models Theory -- 21. Organizational Ecology Theory -- 22. Organizational Justice Theory -- 23. Planned Behavior Theory -- 24. Prospect Theory -- 25. Psychological Contract Theory -- 26. Resource-Based Theory -- 27. Role Theory -- 28. Self-Determination Theory -- 29. Sense making Theory -- 30. Social Capital Theory -- 31. Social Cognitive Theory -- 32. Social Comparison Theory -- 33. Social Exchange Theory -- 34. Social Facilitation Theory -- 35. Social Identity Theory -- 36. Social Network Theory -- 37. Stakeholder Theory -- 38. Structural Contingency Theory --39. Structuration Theory -- 40. Transaction Cost Theory.
Includes bibliographical references and index.
Keywords: BUSINESS; ECONOMICS